Factors Affecting Student’s Financial Literacy (A Study on the Students of the Faculty of Economics and the Faculty of Science and Technology of Sanata Dharma University Yogyakarta) - Erren Egesta; Caecilia Wahyu Estining Rahayu; Christina Heti Tri Rahmawati (Media Ekonomi dan Manajemen, 2021)
This study aims to determine 1) the factors that affect students' financial literacy. The factors include gender, Grade Point Average (GPA) and allowance; 2) the differences in financial literacy between students of the Faculty of Economics and students of the Faculty of Science and Technology. The population in this study were active students from batch 2014-2017 of the Faculty of Economics and the Faculty of Science and Technology, Sanata Dharma University. The sampling technique employed was purposive sampling. The data analysis methods were the Chi-Square test and the Two Independent Sample Test with Mann Whitney Test. The test results show that 1) GPA factor significantly influences students' financial literacy,2) gender and allowance do not affect students' financial literacy,3) there are differences in financial literacy between students of the Faculty of Economics and the Faculty of Science and Technology, in which students of the Faculty of Economics have higher financial literacy level.